Physical mechanisms associated with the intense lightning over Indian region. (27th December 2021) - Murugavel, Palani; Prabha, Thara V.; Pandithurai, Govindan; Gopalakrishnan, Venkatachalam; D. Pawar, Sunil
Abstract: Indian subcontinent receives 80% of its annual total rainfall during Indian summer monsoon (ISM) and since last 100 years the prediction of interannual variability of ISM is limited due to incomplete understanding of various processes and their localized influence on the development of varying scales of convective systems. The present study reports that the intense lightning contributed from the deepest convections occurring over Indian subcontinent are concentrated in four specific regions: (a) southwest coast, (b) Gangetic‐Brahmaputra plain, (c) Himalayan foothills and (d) southeast coast. The spatial and temporal variations of deep convections, size of "convection fractions" and associated physical mechanisms are described. It shows an annual cycle of systematic onset and withdrawal of deep convections and associated lightning depending on region and season. The southwest coast region is developing very deep convections during premonsoon and postmonsoon seasons but less lightning during monsoon. While Arabian Sea sources high moisture to this region in monsoon season, the orographic lift of low‐level westerlies by Western Ghats may effectively assist the warm rain processes and produce highest rainfall, low lightning and low area of deep convections. Highest flash rates, high number of days with lightning and higher area of convection are observed in Gangetic‐Brahmaputra plain but relatively lower rainfall compared to southwest coast region during monsoon. The sustained strong updrafts over the Gangetic‐Brahmaputra plain region are supported by the moisture source from warmer Bay of Bengal, incidence of monsoon trough and the continental heating. Significant lightning activity observed in northwest part of Himalayan foothills during winter is associated with Western Disturbances (WD) phenomena. The diurnal variation of lightning flash rate and size of "convective fraction" in these regions show two modes at 1200 and 1800 UTC and it indicates active day time surface heating and nocturnal cooling processes together contribute to total rainfall. Abstract : The most convections occurring over Indian subcontinent are concentrated in four specific regions. The prevailing seasonal large‐scale conditions respond differently at each of these locations. During Indian summer monsoon, the southwest coast produces very less lightning and the highest rainfall and the Gangetic‐Brahmaputra plain produces highest lightning but relatively less rainfall. The gentle lift of westerlies by Western Ghats assists in southwest coast for effective warm rain processes and less lightning. Whereas the warmer Bay of Bengal, incidence of monsoon trough and the local orography all together assist at Gangetic‐Brahmaputra plain for stronger updraft, formation of very deep convection and high intensity of lightning. This study shows a systematic onset and withdrawal of deep convections and associated lightning depending on location and season. The most convections over Indian subcontinent are concentrated in four specific regions. Southwest cost produces highest rainfall and low lightning during monsoon indicating low clouds and warm rain processes. Gangetic‐Brahmaputra plain produces relatively low rainfall and highest lightning during monsoon indicating high clouds and ice phase processes. This study shows a systematic onset and withdrawal of deep convections and associated lightning depending on location and season.